The growth of homosexual identity : an empirical study from a social work perspective of crisis in sexual identity experienced by a sample of homosexual persons in Cape Town, with special reference to cultural factors - Isaacs, Gordon Michael (Department of Social Development, 2016)
Bibliography: pages 562-602.